The desolations of Devil's Acre - Riggs, Ransom (Riggs, Ransom. Novel of Miss Peregrine's Peculiar Children, 2021)
"The last thing Jacob Portman saw before the world went dark was a terrible, familiar face. Suddenly, he and Noor are back in his grandfather's house. Jacob doesn't know how they escaped from V's loop, but he does know one thing for certain: Caul has returned. Risen from the Library of Souls, Caul and his apocalyptic agenda seem unstoppable. Only one hope remains--deliver Noor to the meeting place of the seven prophesied ones, if they can decipher its secret location"--